The godly image : Christian satisfaction in Aquinas - Cessario, Romanus (Sacra doctrina series (Washington, D.C.), 2020)
"Examines the unique and lasting features of Thomas Aquinas's understanding of Christian satisfaction, centered on the notion of the reformation of the image of God in man"--